Pengaruh Ekstrak Batang Dan Daun Pakis Sayur (Diplazium Esculentum) Terhadap Kadar Hemoglobin, Hematokrit dan Jumlah Eritrosit Pada Tikus Putih Jantan yang Disuntikkan Natrium Nitrit (NaNO2) - Sashmita, Geby; Putra, I Gusti Putu Agus Ferry Sutrisna; Widayanti, Ni Putu (Bali International Scientific Forum, 2020)
Background: Anemia is a decrease in hemoglobin level, hematocrit value and the number of erythrocytes in the body due to a lack of iron intake in the body. One plant that is rich in iron is vegetable ferns (diplazium esculentum). This research was conducted at the Animal Unit Laboratory of the Faculty of Medicine, Udayana University. Objective: To determine the effect of vegetable ferns and stem extracts on hemoglobin levels, hematocrit values and the number of erythrocytes. Method: This study uses true experimental design. Results: The results of this study prove that stem fern extract and vegetable ferns can increase hemoglobin levels, hematocrit values and the number of erythrocytes in experimental male rats with a dose of 0.18 grams, 0.36 grams and 0.72 grams. Conclusion: There was a significant effect on male white mice with anemia treatment after being given stem and vegetable fern leaf extract, where the administration of vegetable fern extracts and ferns with a dose of 0.72 grams resulted in an increase in hemoglobin levels of 52.07%, a hematocrit value of 32, 91% and the number of erythrocytes is 29.41%.